A prospective comparative study of Lichtenstein procedure with and without mesh-fixation for inguinal hernia repair - Kumar, Ravinder; Wani, Hilal A.; Mahesh, Anshuman; Mir, Irfan N. (International Journal of Research in Medical Sciences, 2021)
Background: Repair of inguinal hernia is one of the most common elective operations performed in general surgery worldwide. Mesh-hernioplasty became the gold standard, because of its low recurrence rate in comparison with tissue repairs. The ideal repair must be simple, safe, easy to perform and require minimal dissection which provides enough space, should be cost effective with less hospital stay, less pain and less recurrence. The present study aimed at comparing the effect of mesh fixation and non-fixation in Lichtenstein technique for inguinal hernia repair. Methods: Hundred (100) patients with primary uncomplicated, unilateral inguinal hernia were treated between April 2019 and September 2020. Patients with inguinal hernia underwent Lichtenstein repair with mesh-fixation (group A) (n=50) and non-fixation (group B) (n=50). The mean operative time, post-operative pain score, average hospital study, post-operative complications and recurrence rates were compared between the two groups. Results: Mean operative time in non-fixation group- (group B) (32.24 min) was shorter as compared to fixation group-(Group A) (49.36 min) with a p value of 0.002. Post-operative pain score was lower in (group B) at 12 and 24 hours (3.71±1.409 and 2.2±0.8169) as compared to Group A at 12 and 24 hours (4.77±1.196 and 2.98±1.295) with a p value of <0.0001. The analgesia required in (group B) was less as compared to (group A). The post-operative complication and recurrence rates were almost identical in both the groups, with lesser incidence of groin pain and paresthesias in group B. Conclusions: In Lichtenstein inguinal hernia repair, non-fixation of mesh is safe and preferable option, with less operative time and less postoperative pain.